"Alone in the Rain(bow)": Existential Therapy for Loneliness in LGBTQ + Clients. Issue 1 (1st February 2021) - Ratanashevorn, Rattanakorn; Brown, Emily C.
Abstract: Loneliness and isolation are major concerns for LGBTQ + clients who experience marginalization, discrimination and alienation in society and social networks. These experiences of increased loneliness and isolation can lead to other detrimental mental health outcomes, such as substance abuse, HIV, and suicide. Loneliness and isolation are central concerns of existential therapy which makes this a compatible approach for addressing these issues among LGBTQ + clients. This article uses an existential therapy lens to examine the issue of loneliness among LGBTQ + clients and provides a case illustration to demonstrate its application.